Novel interferonopathies associated with mutations in RIG-I like receptors. (June 2016) - Buers, Insa; Nitschke, Yvonne; Rutsch, Frank
Highlights: Interferonopathies reflect a newly recognised entity with increased type I interferon levels and overlapping phenotypes. In the attached review, we focus on the most recent discoveries of the genetic basis and pathomechanism of interferonopathies associated with mutations in RIG-I like cytoplasmic receptors for double stranded RNA. Mutations in IFIH1 and DDX58 lead to typical and atypical Singleton-Merten syndrome which show a considerable overlap with Aicardi-Goutières syndrome. Abstract: Type I interferonopathies are a relatively new class of inherited autoimmune disorders associated with an inborn elevated interferon response. Activation of cytosolic receptors which recognize viral double stranded RNA including the RIG-I (retinoic acid–inducible gene I) like receptors RIG-I and MDA5 (melanoma differentiation-associated gene 5) has been shown to induce the transcription of type I interferon genes. Within recent years, with the help of next generation sequencing techniques in syndromic families, mutations in the genes encoding for RIG-I and MDA5 have been identified to cause rare diseases including Aicardi-Goutières syndrome, Systemic Lupus Erythematosus in certain individuals as well as classic and atypical Singleton-Merten syndrome. Patients carrying mono-allelic mutations in MDA5 and RIG-I show constitutive activation of the RIG-I receptors and downstream signalling associated with increased type I interferon production. Although differing in the degree of phenotypic expression and severity, the phenotype of these "novel" diseases shows a considerable overlap reflecting their common pathogenetic pathway.